Modalitas Intensional dalam Bahasa Indonesia dan Jawa: Sebuah Analisis Kontrastif - Jimly, A. Syihabuddin Aniq; Hariri, Tatang (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
This study examines intentional modality in Indonesian and Javanese through a contrastive linguistic perspective using a descriptive qualitative design. A corpus of utterances containing intentional markers in Indonesian (e.g., ingin, mau, harap) and Javanese (e.g., pengin, arep, gelem, ngajab, ndongakake) was compiled from documented usage and relevant literature. The data were identified and classified into five meanings—desire, hope, invitation, letting, and request—and analyzed with respect to syntactic distribution, morphological realization, and negation patterns. Comparative mapping was then conducted to determine convergences and divergences across the two languages, including the relative position of markers, the interaction between modality and predicate negation, and form–meaning correspondences. The findings clarify how closely related Austronesian languages encode intentional stance through distinct lexical and morphosyntactic resources, and they provide an empirical basis for contrastive linguistics, language learning, and grammatical description. This discussion also outlines implications for interpreting Indonesian–Javanese texts.